1995
DOI: 10.1097/00000542-199502000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Epidural and Intravenous Fentanyl Produce Equivalent Effects during Major Surgery 

Abstract: There appears to be no clinical advantage to epidural administration of fentanyl over intravenous administration during anesthesia for major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Median time [IQR (range)] to awakening ( Fig. 3) was 8 min [4.5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)] in the epidural group and 20 min [12.5 (7-34)] in the intravenous group (P < 0.001); the ANCOVA model rules out the possibility that the differences were related to the dose of propofol. When evaluating the time to analgesia request ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Median time [IQR (range)] to awakening ( Fig. 3) was 8 min [4.5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)] in the epidural group and 20 min [12.5 (7-34)] in the intravenous group (P < 0.001); the ANCOVA model rules out the possibility that the differences were related to the dose of propofol. When evaluating the time to analgesia request ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 Many authors hold that epidural administration of fentanyl is more effective than intravenous administration, suggesting a spinal site of action; [2][3][4][5][6] others claim that both routes of administration provide a similar degree of analgesia, suggesting a supraspinal site of action after vascular absorption from the epidural space and redistribution from there to the brain. [7][8][9][10] If the latter hypothesis is correct, epidural fentanyl should provide no benefit over systemic (i.e. intravenous) administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Guinard et al found that fentanyl plasma concentration and the need for supplemental analgesia were similar in patients receiving fentanyl by epidural route and IV bolus supporting so a systemic mechanism of action. However the average dose of epidural fentanyl studied by these authors was larger than that studied by other investigators [48]. Menigaux et al studied postoperative pain management with IV and epidural sufentanil administered as small (5 mcg) repeated boluses and showed that plasma sufentanil concentrations were similar in both groups thus concluding that epidural sufentanil produced analgesia by systemic mechanism.…”
Section: Opioidsmentioning
confidence: 85%
“…Cumulative postoperative opioid consumption was reported in oral morphine equivalents over 24-h periods for the first 72 h. Fentanyl delivered through the neuraxial route was considered equivalent to intravenous fentanyl and converted to oral morphine equivalents using defined scales [Table 1]. [1617] Secondary objectives were to determine whether the PVB group differed from the TE or PCA groups in pain scores, the incidence of nausea and vomiting, the frequency of antiemetic administration, time to first oral intake after PACU discharge, intraoperative hypotension, and intraoperative administration of catecholamine.…”
Section: Methodsmentioning
confidence: 99%